Prussian blue positive electrode material, preparation method thereof, positive plate and sodium ion battery
By using aqueous solvents and common electrode homogenization process in the preparation of Prussian blue materials, the problem of structural instability in the synthesis process of Prussian blue materials is solved, and a low-cost and high-performance sodium ion battery preparation is achieved, which meets the requirements of green and environmental protection.
Patent Information
- Application Number
- CN202510483949.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-08-26
AI Technical Summary
The traditional sodium ion battery positive electrode material Prussian blue introduces crystallized water and organic solvents during the synthesis process, resulting in structural instability, increasing costs and environmental pollution, and toxic solvents affect health.
Water is used instead of organic solvents, combined with conductive agents and binders, and directly share the Prussian blue material with the electrode homogenization process to prepare Prussian blue positive electrode material with uniform particles and low defects, eliminating the separate baking steps.
Reduce energy consumption and production costs, improve electronic conductivity, and obtain high-performance Prussian blue sodium ion batteries, reflecting the concept of green and environmental protection development.
Smart Images

Figure CN120545358A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular to a Prussian blue positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Sodium-ion batteries (Na-ion batteries) are a potential candidate for future large-scale energy storage applications due to their abundant resources, low cost, environmental friendliness, and similar electrochemical energy storage mechanism to lithium-ion batteries. However, the high cost and inadequate rate performance and cycling stability of conventional Na-ion battery cathode materials (such as layered oxides and polyanion cathodes) significantly restrict their practical application.
[0003] Prussian blue analogs (PBs), ferrocyanide compounds with a three-dimensional open-frame structure, have been widely used in recent years as cathode materials for sodium-ion batteries due to their low cost, abundant reserves, environmental friendliness, and excellent sodium-ion energy storage performance. The unique lattice structure of Prussian blue materials provides efficient and rapid three-dimensional diffusion channels for the insertion and extraction of sodium ions, resulting in a theoretical capacity of up to 170 mAh / g, demonstrating significant advantages in rate capability and long cycle life.
[0004] Currently, Prussian blue materials are typically synthesized by coprecipitation in an aqueous environment. During the nucleation and growth process, a certain amount of crystallized and adsorbed water is inevitably introduced, which must be removed by heating. Traditional homogenization processes use organic solvents such as N-methylpyrrolidone (NMP), requiring secondary heating of the electrode after coating to remove the organic solvent and water. Water in the Prussian blue material undergoes an introduction-removal-adsorption-removal cycle, repeatedly migrating within the Prussian blue crystals. This can lead to structural defects and instability, resulting in rapid capacity decay. Furthermore, the use of toxic organic solvents can pose health risks to processing personnel, increase product costs, and potentially cause a degree of environmental pollution. Therefore, developing a low-cost, environmentally friendly method for preparing Prussian blue cathode slurries is of great significance. Summary of the Invention
[0005] In view of this, embodiments of the present invention provide a Prussian blue positive electrode material and a preparation method thereof, a positive electrode sheet, and a sodium ion battery.
[0006] This application adopts the following technical solutions: The present invention provides a method for preparing a Prussian blue positive electrode material, comprising: Mixing ferrous sulfate, a complexing agent, and deionized water to obtain a first solution; mixing sodium ferrocyanide decahydrate and deionized water to obtain a second solution; dropping the second solution into the first solution to perform a precipitation reaction, thereby obtaining a Prussian blue main material slurry; adding conductive agent multi-walled carbon nanotubes and conductive carbon black to carboxymethyl cellulose slurry in sequence to obtain a first homogenized slurry; The Prussian blue main material slurry is introduced into the first homogenized slurry, and the second homogenized slurry is obtained after stirring.
[0007] Styrene-butadiene rubber is added to the second homogenized slurry, and the mixture is stirred to obtain a Prussian blue positive electrode material.
[0008] Optionally, the molar ratio of Fe element to Mn element in the first solution is not less than 1:2.
[0009] Optionally, the molar range of the complexing agent in the first solution is Fe 2+ and Mn 2+ 1 to 1.5 times the total number of moles.
[0010] Optionally, the concentration range of the second solution is 0.1 mol / L~0.5 mol / L.
[0011] Optionally, during the process of dripping the second solution into the first solution for precipitation reaction, the reaction temperature ranges from 25° C. to 90° C., and the pH value ranges from 5 to 6.
[0012] Optionally, the solid content of the carboxymethyl cellulose slurry is in the range of 5% to 20%.
[0013] The present invention also provides a Prussian blue positive electrode material, which is prepared by adopting the above-mentioned preparation method of the Prussian blue positive electrode material.
[0014] The present invention also provides a positive electrode sheet, comprising a current collector and a positive electrode material coated and dried on the surface of the current collector, wherein the positive electrode material is the above-mentioned Prussian blue positive electrode material.
[0015] The present invention also provides a sodium ion battery, comprising the above-mentioned positive electrode sheet.
[0016] In summary, the advantages and beneficial effects of the present invention are: The present invention provides a Prussian blue positive electrode material, a preparation method thereof, a positive electrode sheet, and a sodium ion battery. The preparation method of the Prussian blue positive electrode material uses the synthesis process of the Prussian blue material and its electrode slurry process in common, and simultaneously prepares a Prussian blue positive electrode material with uniform particles and low defects, eliminating the process of separately baking the synthesized material, and significantly reducing energy consumption. Water is used to replace traditional organic solvents, avoiding the impact of toxic solvents on human health and the environment, and also eliminating the cost of solvent recovery equipment. Moreover, the use of water as a solvent adjusts the surface and interfacial groups, thereby improving the electronic conductivity of the positive electrode sheet prepared from the Prussian blue positive electrode material obtained by this method, and obtaining a high-performance Prussian blue sodium ion battery. The direct sharing of the previous and subsequent processes and the use of water as a solvent improve the systematization and intensification of the equipment, reduce costs, and embody the concept of green and environmentally friendly development. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work, but they should fall within the scope of protection of this application.
[0018] Figure 1 A schematic flow chart of a method for preparing a Prussian blue cathode material provided in an embodiment of the present invention; Figure 2 A SEM diagram of a Prussian blue cathode material provided in an embodiment of the present invention; Figure 3 An XRD diagram of a Prussian blue cathode material provided in an embodiment of the present invention; Figure 4 A schematic diagram of a charge and discharge curve of a sodium ion battery provided in an embodiment of the present invention; Figure 5 A schematic diagram of a cycle curve of a sodium ion battery provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0019] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0020] It should be understood that the embodiments described are only a portion of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0021] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "an", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.
[0022] The present invention provides a method for preparing a Prussian blue positive electrode material, comprising: Step S100, mixing ferrous sulfate, manganese sulfate, a complexing agent and deionized water to obtain a first solution; Step S200, mixing sodium ferrocyanide decahydrate and deionized water to obtain a second solution; Step S300, dropping the second solution into the first solution to perform a precipitation reaction to obtain a Prussian blue main material slurry; Step S400, adding conductive agent multi-walled carbon nanotubes and conductive carbon black to carboxymethyl cellulose slurry in sequence to obtain a first homogenized slurry; Step S500, passing the Prussian blue main material slurry into the first homogenized slurry, and stirring to obtain a second homogenized slurry; Step S600: adding styrene-butadiene rubber to the second homogenized slurry, and stirring to obtain a Prussian blue positive electrode material.
[0023] Specifically, step S10 is performed to mix ferrous sulfate, manganese sulfate, a complexing agent and deionized water to obtain a first solution.
[0024] In an embodiment of the present invention, the step of obtaining the first solution includes: Step S101, adding deionized water, ferrous sulfate, manganese sulfate and sodium citrate into a first reaction kettle to obtain a first mixture; Step S102: stirring the first mixture until it is completely dissolved to obtain a clear first solution.
[0025] In the embodiment of the present invention, Fe 2+ The concentration and release rate directly affect the crystallinity and vacancy defects of Prussian blue, and the molar ratio of Fe element to Mn element in the first solution is controlled to be no less than 1:2.
[0026] Ferrous sulfate and manganese sulfate provide Fe 2+ and Mn 2+ source, used to participate in the subsequent formation of the Prussian blue lattice. In the subsequent reaction, Fe 2+ and Mn 2+ Coordinates with the cyanide group in sodium ferrocyanide decahydrate to form Na2Mn x Fe 1-x (Fe(CN)6)·nH2O blue precipitate.
[0027] Manganese sulfate is used as a dopant to provide Mn 2+ , partially replacing the Fe sites to form a manganese-doped Prussian blue analogue material to enhance the electrochemical activity of the material.
[0028] In the embodiment of the present invention, the complexing agent is used to adjust Fe 2+ With [Fe(CN)6] 4− , or Fe 2+ 、Mn 2+ With [Fe(CN)6] 4− The complexation rate has a regulating effect on the crystal structure, crystalline water content, morphology and size of the synthetic materials.
[0029] In an embodiment of the present invention, the complexing agent is sodium citrate.
[0030] In other embodiments, the complexing agent is one of disodium EDTA, sodium tartrate, and sodium oxalate.
[0031] In the embodiment of the present invention, the molar range of sodium citrate in the first solution is Fe 2+ and Mn 2+ 1 to 1.5 times the total molar amount of Fe, the sodium citrate regulates 2+ and Mn 2+ The release rate of sodium citrate and Fe 2+ and Mn 2+ The chelating strength is moderate and can balance [Fe(CN)6] 4− with Fe 2+ / Mn 2+ The bonding process optimizes the lattice integrity and avoids Fe 2+ / Mn 2+ Too fast precipitation leads to Na vacancy defects and crystallization water in the Prussian blue lattice.
[0032] In other embodiments, the first solution may not include manganese sulfate. When manganese sulfate is not included, the molar number of sodium citrate in the first solution is Fe 2+ 1~1.5 times the total number of moles.
[0033] In an embodiment of the present invention, the stirring rate of the first mixture is 100 r / min to 200 r / min.
[0034] Step S200 is performed to mix sodium ferrocyanide decahydrate and deionized water to obtain a second solution.
[0035] In an embodiment of the present invention, the step of obtaining the second solution includes: Step S201, adding deionized water and sodium ferrocyanide decahydrate into a second reaction kettle to obtain a second mixture; Step S202: stirring the second mixture until it is completely dissolved to obtain a clear first solution.
[0036] In an embodiment of the present invention, the concentration of the second solution is 0.1 mol / L to 0.5 mol / L.
[0037] In an embodiment of the present invention, the stirring rate of the second mixture is 100 r / min to 200 r / min.
[0038] In the embodiment of the present invention, sodium ferrocyanide decahydrate directly provides [Fe(CN)6] 4− Ligand, [Fe(CN)6] 4− with Fe 2+ / Mn 2+ Formation of Prussian blue cubic structure Na2Mn by coordination bond x Fe 1-x The concentration of (Fe(CN)6)·nH2O and sodium ferrocyanide decahydrate directly affects the nucleation and growth of Prussian blue.
[0039] Step S300 is performed to drop the second solution into the first solution to perform a precipitation reaction to obtain a Prussian blue main material slurry.
[0040] In an embodiment of the present invention, stirring is maintained during the process of dripping the second solution into the first solution for precipitation reaction, so that the second solution drops are quickly and evenly mixed with the first solution without causing a sudden concentration change, thereby avoiding excessive initial concentration, which leads to excessive complexation and the formation of more structural defects.
[0041] In an embodiment of the present invention, during the process of dripping the second solution into the first solution for precipitation reaction, the reaction temperature ranges from 25°C to 60°C, which is used to adjust the complexation rate of the metal ion and the ligand ferrocyanide, and avoid the temperature affecting the content of crystal water in the material, which is not conducive to the integrity of the crystal structure.
[0042] In the embodiment of the present invention, the pH value ranges from 5 to 6, maintaining neutrality to acidity, providing a complexing environment for the complexing agent. Different complexing environments are provided depending on the complexing agent selected.
[0043] In the embodiment of the present invention, during the precipitation reaction of the second solution being dropped into the first solution, N2 is kept as a protective gas to prevent the first solution droplets and the Fe in the second solution from 2+ Oxidation leads to reaction failure.
[0044] In step S400 , conductive agents multi-walled carbon nanotubes (CNTs) and conductive carbon black (SP) are sequentially added into a carboxymethyl cellulose (CMC) slurry to obtain a first homogenized slurry.
[0045] In an embodiment of the present invention, multi-walled carbon nanotubes are first added to the carboxymethyl cellulose and stirred for a period of time to allow the multi-walled carbon nanotubes to be better dispersed in the carboxymethyl cellulose.
[0046] The high specific surface area and electrical conductivity of the multi-walled carbon nanotubes are used to improve the electron transmission efficiency of Prussian blue, inhibit the agglomeration of nanoparticles, and enhance the mechanical stability of the subsequently obtained Prussian blue positive electrode material.
[0047] The conductive carbon black serves as a conductive additive to fill the gaps between the Prussian blue and the multi-walled carbon nanotubes, further reducing the resistance of the subsequently obtained Prussian blue positive electrode material and improving the overall conductivity.
[0048] In an embodiment of the present invention, the conductive carbon black is spherical.
[0049] Carboxymethyl cellulose is used as a binder to fix the Prussian blue and multi-walled carbon nanotubes / conductive carbon black, thereby ensuring the uniformity of the first homogenized slurry and enhancing the mechanical strength of the Prussian blue positive electrode material.
[0050] In an embodiment of the present invention, the solid content of the carboxymethyl cellulose slurry ranges from 5% to 20%. The thickening properties of the carboxymethyl cellulose slurry increase the viscosity of the first homogenized slurry, thereby adjusting the fluidity of the liquid. Furthermore, by uniformly dispersing the carboxymethyl cellulose in the first homogenized slurry, the agglomeration of multi-walled carbon nanotubes and conductive carbon black particles is prevented, thereby improving the stability of the first homogenized slurry and the conductivity and cycle performance of the electrode. Furthermore, carboxymethyl cellulose is water-soluble, and using water as a solvent avoids the use of organic solvents.
[0051] Furthermore, in an embodiment of the present invention, the solid content of the carboxymethyl cellulose slurry is 10%.
[0052] Step S500 is executed to introduce the Prussian blue main material slurry into the first homogenized slurry, and the mixture is stirred to obtain a second homogenized slurry.
[0053] In an embodiment of the present invention, the Prussian blue main material slurry is introduced into the first homogenized slurry by pumping.
[0054] In an embodiment of the present invention, the Prussian blue main material slurry and the first homogenized slurry are stirred for 30 minutes.
[0055] Step S600 is performed to add styrene-butadiene rubber (SBR) into the second homogenized slurry, and the mixture is stirred to obtain a Prussian blue positive electrode material.
[0056] In an embodiment of the present invention, the Prussian blue positive electrode material is a slurry containing Prussian blue. In the subsequent process of preparing the positive electrode sheet, the Prussian blue positive electrode material, that is, the slurry containing Prussian blue, is directly coated on the current collector and dried to obtain the positive electrode sheet.
[0057] Styrene-butadiene rubber and carboxymethyl cellulose work together to improve the flexibility and adhesion of the slurry, preventing the volume expansion of the Prussian blue positive electrode material during the charge and discharge process from causing the material to fall off. The elastic properties of styrene-butadiene rubber can buffer the stress changes of the Prussian blue positive electrode material during the electrochemical cycle.
[0058] In an embodiment of the present invention, the second homogenized slurry and the styrene-butadiene rubber (SBR) are stirred for 1 hour.
[0059] The present invention uses the synthesis process of the Prussian blue material in common with its electrode slurry process to simultaneously prepare a Prussian blue positive electrode material with uniform particles and low defects, eliminating the process of separately baking the synthesized material and significantly reducing energy consumption. Water is used to replace traditional organic solvents, avoiding the impact of toxic solvents on human health and the environment, and also eliminating the cost of solvent recovery equipment. Moreover, the use of water as a solvent adjusts the surface and interfacial groups, thereby improving the electronic conductivity of the positive electrode sheet prepared from the Prussian blue positive electrode material obtained by this method, and obtaining a high-performance Prussian blue sodium-ion battery. The direct sharing of the previous and next processes and the use of water as a solvent improve the systematization and intensification of the equipment, reduce costs, and embody the concept of green and environmentally friendly development.
[0060] An embodiment of the present invention further provides a Prussian blue positive electrode material, which is prepared using the above-mentioned method for preparing a Prussian blue positive electrode material.
[0061] In the embodiment of the present invention, Figure 2~Figure 3 As shown, the obtained Prussian blue positive electrode material presents a small particle cubic morphology, a monoclinic structural feature, a higher specific surface area and crystal integrity. Based on the Prussian blue positive electrode material, it can provide higher sodium reaction active sites for the prepared sodium ion battery and achieve good structural stability.
[0062] An embodiment of the present invention further provides a positive electrode sheet, comprising a current collector and a positive electrode material coated and dried on the surface of the current collector, wherein the positive electrode material is the above-mentioned Prussian blue positive electrode material.
[0063] In the embodiment of the present invention, the cathode sheet has a cubic morphology and a monoclinic structure. After coating, the anode sheet is dried at 80°C to remove adsorbed water and then dried at a certain temperature to remove interstitial water in the cathode sheet.
[0064] In an embodiment of the present invention, the positive electrode sheet is obtained after the Prussian blue positive electrode material is coated on the surface of the current collector and dried. The drying temperature range is 150° C. to 220° C., and the drying time range is 12 h to 72 h.
[0065] In an embodiment of the present invention, the current collector includes aluminum foil, copper foil or other suitable materials.
[0066] An embodiment of the present invention further provides a sodium ion battery, comprising the above-mentioned positive electrode sheet.
[0067] In the embodiment of the present invention, Figure 4~Figure 5 As shown in the figure, the charge and discharge curve of the prepared Prussian blue full battery shows an obvious platform at around 3.3 V. After 600 cycles, the capacity retention rate is as high as more than 90%, and the cycle stability is conveniently maintained at the existing level. Specific embodiment 1: Step S11, FeSO4, MnSO4, sodium citrate and deionized water are mixed to obtain a first solution, wherein the molar ratio of Fe:Mn is 1:1, the molar number of sodium citrate is Fe 2+ / Mn 2+ 1.2 times the molar number, stirring at 200 r / min until completely dissolved; Step S12, dissolving Na4Fe(CN)6·10H2O and deionized water to obtain a second solution, wherein the concentration of Na4Fe(CN)6 is 0.5 mol / L, and the solution is stirred at a speed of 200 r / min; Step S13, dripping the second solution into the first solution to perform a precipitation reaction to obtain a Prussian blue main material slurry, wherein the second solution is dripped into the first solution at a rate of 10 mL / min, the reaction temperature is 50° C., the pH value is 5.5, and N2 is introduced for protection; Step S14: adding conductive multi-walled carbon nanotubes and conductive carbon black to the carboxymethyl cellulose slurry in sequence to obtain a first homogenized slurry, wherein the solid content of the carboxymethyl cellulose slurry is 10%, the content of the multi-walled carbon nanotubes is 0.5wt%, and the content of the conductive carbon black is 2wt%. Step S50, passing the Prussian blue main material slurry into the first homogenized slurry, and stirring to obtain a second homogenized slurry, wherein the stirring time is 30 minutes; Step S60: adding styrene-butadiene rubber to the second homogenized slurry and stirring to obtain a Prussian blue positive electrode material, wherein the concentration of the styrene-butadiene rubber is 2 wt % and the stirring time is 1 h.
[0069] The Prussian blue positive electrode material prepared by the method of this embodiment has a cubic morphology and a monoclinic structure. After coating, it is heated at 80°C to remove adsorbed water, and then dried at 150°C to remove the interstitial water in the Prussian blue to obtain a positive electrode sheet. Then, a hard carbon negative electrode is used to prepare a negative electrode sheet according to the same process and assembled into a Prussian blue sodium ion battery. Specific embodiment 2 Step S11, FeSO4, MnSO4, sodium citrate and deionized water are mixed to obtain a first solution, wherein the molar ratio of Fe:Mn is 1:1.5, the molar number of sodium citrate is Fe 2+ / Mn 2+ 1.2 times the molar number, stirring at 100 r / min until completely dissolved; Step S12, dissolving Na4Fe(CN)6·10H2O and deionized water to obtain a second solution, wherein the concentration of Na4Fe(CN)6 is 0.5 mol / L, and the solution is stirred at a speed of 100 r / min; Step S13, dripping the second solution into the first solution to perform a precipitation reaction to obtain a Prussian blue main material slurry, wherein the second solution is dripped into the first solution at a rate of 10 mL / min, the reaction temperature is 50° C., the pH is 6, and N2 is introduced for protection; Step S14, adding conductive agent multi-walled carbon nanotubes and conductive carbon black to the carboxymethyl cellulose slurry in sequence to obtain a first homogenized slurry, wherein the solid content of the CMC slurry is 10%, the content of the multi-walled carbon nanotubes is 0.5wt%, and the content of the conductive carbon black is 2wt%; Step S50, passing the Prussian blue main material slurry into the first homogenized slurry, and stirring to obtain a second homogenized slurry, wherein the stirring time is 30 minutes; Step S60: adding styrene-butadiene rubber to the second homogenized slurry and stirring to obtain a Prussian blue positive electrode material, wherein the concentration of the styrene-butadiene rubber is 2 wt % and the stirring time is 1 h.
[0071] The Prussian blue positive electrode material prepared using the method of this example was coated onto copper foil or its surface and dried at 220°C to obtain a positive electrode sheet. A hard carbon negative electrode was used, and the negative electrode sheet was prepared using the same process. The resulting Prussian blue sodium-ion battery was assembled. The charge-discharge curve of the prepared Prussian blue full battery exhibited a distinct plateau around 3.3 V, and after 600 cycles, the capacity retention rate exceeded 90%.
[0072] By combining the synthesis of Prussian blue materials with the electrode homogenization process, this method significantly reduces energy consumption and production costs. Furthermore, the use of water as a solvent embodies the concept of green and environmentally friendly development. The resulting Prussian blue sodium-ion battery exhibits excellent rate capability and cycle stability, demonstrating broad application prospects.
[0073] The technical features of the above embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0074] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the claims appended to this application.
Claims
1. A method for preparing a Prussian blue positive electrode material, characterized in that: include: Mixing ferrous sulfate, a complexing agent, and deionized water to obtain a first solution; mixing sodium ferrocyanide decahydrate and deionized water to obtain a second solution; dropping the second solution into the first solution to perform a precipitation reaction, thereby obtaining a Prussian blue main material slurry; adding conductive agent multi-walled carbon nanotubes and conductive carbon black to carboxymethyl cellulose slurry in sequence to obtain a first homogenized slurry; The Prussian blue main material slurry is introduced into the first homogenized slurry, and the second homogenized slurry is obtained after stirring. Styrene-butadiene rubber is added to the second homogenized slurry, and the mixture is stirred to obtain a Prussian blue positive electrode material.
2. The method for preparing a Prussian blue positive electrode material according to claim 1, wherein: The first solution also includes manganese sulfate.
3. The method for preparing a Prussian blue positive electrode material according to claim 2, wherein: The molar ratio of Fe element to Mn element in the first solution is not less than 1:
2.
4. The method for preparing a Prussian blue positive electrode material according to claim 2, wherein: The molar range of the complexing agent in the first solution is Fe 2+ and Mn 2+ 1~1.5 times the total number of moles.
5. The method for preparing a Prussian blue positive electrode material according to claim 1, wherein: The concentration of the second solution ranges from 0.1 mol / L to 0.5 mol / L.
6. The method for preparing a Prussian blue positive electrode material according to claim 1, wherein: In the process of dripping the second solution into the first solution for precipitation reaction, the reaction temperature ranges from 25° C. to 90° C., and the pH value ranges from 5 to 6.
7. The method for preparing a Prussian blue positive electrode material according to claim 1, wherein: The solid content of the carboxymethyl cellulose slurry is in the range of 5% to 20%.
8. A Prussian blue positive electrode material, characterized in that The method for preparing a Prussian blue positive electrode material according to any one of claims 1 to 7 is used.
9. A positive electrode sheet, characterized in that: The invention comprises a current collector and a positive electrode material coated and dried on the surface of the current collector, wherein the positive electrode material is a Prussian blue positive electrode material as claimed in claim 7.
10. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet as claimed in claim 9.